Suburbia’s "crime experts": the neo-conservatism of control theory and the ethos of crime - Preparata, Guido Giacomo (Critical criminology, 2013)
This essay tackles the relationship between morality and crime by way of the debate surrounding Travis Hirschi’s double contribution to so-called "control theory," first as "social bonding theory," and subsequently as a "general theory" of crime. The assessment conducted herein construes the first version of "control" as an expression of patriotism, and its late formulation, on account of its emphasis on varying individual levels of self-mastery, as an implicit reaffirmation of the inevitability of class division. Over the years, the fixation with "self-control" has become a rubric for the suburban anxieties of an upper-middle class surrounded by expanding (ghetto) poverty and plagued by familial dysfunction and the alienation of its own offspring. In the final analysis, these reflections form the basis for a general reformulation, inspired by the sociology of Thorstein Veblen, of the relationship between class and crime and condign punishment by leveraging the notion of ethos (a common mindset peculiar to each class), and proving thereby that crime is systematically determined by this very mindset, which is the spiritual complement to class formation, rather than by the conventionally classless categories of rational self-interest or idiosyncratic proneness to violence.